Structural controls of the Domuyo geothermal field, Southern Andes (36°38′S), Argentina - Galetto, Antonella Tamara (2018)
Geothermal fields in subduction-related orogens are closely linked to areas characterized by young magmatic and tectonic activity, both in arc- and back-arc settings. The spatio-temporal interaction of Quaternary volcanic complexes with regional extensional and transtensional structures might favor a hydrothermal circuit between meteoric water and magmatic fluids. This study encompasses a kinematic analysis of fault structures from the high-enthalpy system located at the western flank of the Domuyo volcano in Argentina. An analysis of remote sensing data was applied to detect regional lineaments, lineament density, and to identify fracture patterns possibly associated with the different deformational stages documented in the area. These results were combined with detailed fracture analysis and kinematic study of mesoscale faults, as well as existing geological, structural, and geophysical data. The integration suggests that the fluid dynamics of the Domuyo geothermal field are directly conditioned by pre-existing basement structures that were reactivated as normal faults during Pliocene-to-Quaternary times. Furthermore, the intensely fracture late Triassic - early Jurassic units are interpreted as the potential level for the reservoir. The fault reactivation was likely associated with the accommodation of regional extension along pre-existing fault structures, and locally enhanced by hydrothermal effects of the Domuyo geothermal field.